Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities